2015
DOI: 10.1111/str.12154
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Added Mass in the Composite Plate Structure Based on Wavelet Packet Transform

Abstract: A new concept has been introduced that the combination of rotational mode shape with two‐dimensional wavelet packet transform to detect the added mass (damage) in a glass fibre reinforced polymer composite plate structure. Wavelet packet transform is an advanced signal processing tool that can magnify the abnormality features in the signal. Rotational mode shapes are sensitive to damage in beam and plate structures. The proposed method employs an added mass, which slides to different locations to alter the loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The extension of the method to composite plates is another challenging issue that could be investigated. In this regard, it should be mentioned the recent contribution by Rajendran and Srinivasan [13] on the identification of an added mass in a glass fibre reinforced polymer composite plate by using a combination of rotational mode shape information with wavelet transform analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The extension of the method to composite plates is another challenging issue that could be investigated. In this regard, it should be mentioned the recent contribution by Rajendran and Srinivasan [13] on the identification of an added mass in a glass fibre reinforced polymer composite plate by using a combination of rotational mode shape information with wavelet transform analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Dinh et al [24] identified the mass, damping coefficient, and stiffness of structures based on the correlation between the structural modal information and additional masses. Rajendran et al [25] attached a mass to different locations of a composite plate structure to change the dynamic characteristics. This allowed us to obtain the rotational bending mode shapes to identify damage.…”
Section: Introductionmentioning
confidence: 99%
“…Such effects results from impact damage and would change certain features in the testing image of a damaged sample compared to the one before impact. The new captured image will display a pattern which differ from a reference image texture, color or intensity, among others and can be used to establish level and magnitude of damage and component validity as a function of feature distribution change [15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%